2007
DOI: 10.1177/0146167207303016
|View full text |Cite
|
Sign up to set email alerts
|

Framing Inequity Safely: Whites' Motivated Perceptions of Racial Privilege

Abstract: Racial inequity was theorized to threaten Whites' self-image when inequity is framed as White privilege but not when framed as anti-Black discrimination. Manipulations of Whites' need for self-regard were hypothesized to affect their perceptions of White privilege but not of anti-Black discrimination. In Experiment 1, White participants reported less privilege when given threatening (vs. affirming) feedback on an intelligence or personality test; in contrast, perceptions of anti-Black discrimination were unaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
219
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(231 citation statements)
references
References 42 publications
(61 reference statements)
10
219
0
2
Order By: Relevance
“…Prior research indicates that the manipulation of similarity we used enhances the motivational salience of these types of estimates (18,46,47); however, the observed results could have been due to different psychological component processes stemming from the similarity prime, including the activation of a Black family of a similar socioeconomic background as participants, which would also lead to the emergence of greater overestimates of economic equality than found without this similarity frame. Future research should not only examine the veracity of this and other alternative explanations for the effects of this similarity manipulation but also consider other methods of manipulating the motivation to perceive racial equality, such as threats to the American racial, socioeconomic, or political system (21,22,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research indicates that the manipulation of similarity we used enhances the motivational salience of these types of estimates (18,46,47); however, the observed results could have been due to different psychological component processes stemming from the similarity prime, including the activation of a Black family of a similar socioeconomic background as participants, which would also lead to the emergence of greater overestimates of economic equality than found without this similarity frame. Future research should not only examine the veracity of this and other alternative explanations for the effects of this similarity manipulation but also consider other methods of manipulating the motivation to perceive racial equality, such as threats to the American racial, socioeconomic, or political system (21,22,48).…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that inducing a self-protective motivation to perceive societal outcomes as fair increases overestimates of general socioeconomic mobility in society (17,18) and may also encourage greater misperceptions of the extent to which societal wealth is distributed equitably across income quintiles (19) or salaries are distributed equitably between major company chief executives and unskilled workers (20). Similarly, motives to perceive the world as fair have been shown to lead White Americans to deny race-based societal privilege (21,22) and may contribute to the tendency for White respondents to be three times as likely as Black respondents to conclude that race relations have improved in America (3). Taken together, this research suggests that motivated beliefs about societal fairness-which tend to be highest among high-status members of society-will predict overestimates of racial economic equality.…”
mentioning
confidence: 99%
“…In the case of Katrina, claims that racism tainted relief efforts may promote experience of collective guilt (Wohl, Branscombe, & Klar, 2006), threaten White Americans' sense that they are citizens of a nonracist society, or threaten the perceived legitimacy of a social order that promotes White privilege (Lowery, Knowles, & Unzueta, 2007). Evidence suggests that White Americans are motivated to deny claims about racism as a means to defend against such threats Adams, Tormala, & O'Brien, 2006).…”
mentioning
confidence: 99%
“…Other studies have demonstrated that self-affirmation can increase Whites' willingness to perceive the existence of racism across a variety of scenarios, 29 to acknowledge the existence of institutional racism, 30 and to acknowledge "white privilege." 31 This suggests that giving providers the opportunity to affirm their worth prior to or as part of communication about unintentional provider bias might help reduce defensiveness to potentially threatening messages. Findings such those of Moskowitz et al, underscore the importance of addressing providers bias, in order to reduce racial healthcare disparities.…”
mentioning
confidence: 99%